Morfometria, uso e ocupação do solo em bacias hidrográficas na região neotropical: estratégias visando a preservação ambiental - Silva, Jhony Ferry Mendonça da (2017)
Knowledge of morphometry, relief, drainage network and land use and occupation in watersheds is important for decision making in environmental projects. Therefore, the objective of the study was to analyze the morphometry and to identify the characteristics of the relief in nine tributary watersheds of the Iguaçu River, besides characterizing slopes, drainage network, and land use and occupation. The analyzed basins presented generally elongated forms, being little susceptible to floods, with medium undulated relief, have intermediate to poor drainage. They have sinuosity from intermediate to high. The classification obtained values of accuracy by the Kappa coefficient of 99.4 to 99.9%. The cluster analysis revealed that the Floriano River basin presents greater environmental preservation, followed by the Silva Jardim and Gonçalves Dias river basins. For the Capanema, Cotejipe, Andrada and Santo Antônio rivers, they have intermediate environmental preservation, and the basins of the Monteiro and Sarandi rivers have less environmental preservation, with greater distance between them. Studies using geomorphological analysis techniques multispectral classification in watersheds are essential, allowing systematic evaluation of hydrographic regions on a large scale and thus generate important information for decision making aiming at the preservation and management of these regions.